How to measure Corporate Bond Liquidity? - Patrick Houweling; Albert Mentink; Ton Vorst (Tinbergen Institute, 2003)
We consider eight different measures (issued amount, coupon, listed, age, missingprices, price volatility, number of contributors and yield dispersion) to approximate corporatebond liquidity and use a five-variable model to control for maturity, credit and currencydifferences between bonds. The null hypothesis that liquidity risk is not priced in our dataset of euro corporate bonds is rejected for seven out of eight liquidity measures. We findsignificant liquidity premia, ranging from 9 to 24 basis points. A comparison test betweenliquidity measures shows that some ways to measure liquidity are better than others.
Keywords: C13; G12; 330; liquidity; corporate bonds; Fama-French model; euro market.; Unternehmensanleihe; Geldsubstitut; Messung